1997
DOI: 10.1164/ajrccm.155.6.9196091
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor antagonists inhibit antigen-induced lung inflammation in mice.

Abstract: In this study, we have examined the effect of endothelin (ET) receptor antagonists on lung granulocyte inflammation after antigen challenge in sensitized mice. The antagonists used were BQ-123, an ETA antagonist, BQ-788, an ETB antagonist, and SB209670, an ET(A&B) antagonist. Thirty minutes prior exposure to aerosolized ovalbumin, ET antagonists (50 pmol/mouse) were administered directly into the lungs of sensitized Balb/c mice via the intranasal route. BQ-123 and SB209670 significantly decreased eosinophil nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
40
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 19 publications
9
40
2
Order By: Relevance
“…For example, the endothelin receptor antagonist BQ-123 reduced the late, but not the early, antigen-induced reduction in airflow response in allergic sheep (26) and guinea pigs (38). The involvement of ET-1 in the late-phase allergic response, which is associated with the migration of inflammatory cells into the airways, is in accord with the recent findings from several independent groups that endothelin receptor antagonists inhibit the antigeninduced influx of eosinophils into the airways and bronchoalveolar lavage fluid (12,15,31).In addition to its effects on eosinophil recruitment into the airways, ET-1 has many other purported actions within the airways that may promote inflammation and airflow obstruction. For example, ET-1 stimulates the release of a range of proinflammatory cytokines [such as interleukin (IL)-6, IL-1␤, and tumor necrosis factor-␣] and promotes microvascular leakage, mucous secretion, and collagen deposition within the airways (16).…”
supporting
confidence: 82%
“…For example, the endothelin receptor antagonist BQ-123 reduced the late, but not the early, antigen-induced reduction in airflow response in allergic sheep (26) and guinea pigs (38). The involvement of ET-1 in the late-phase allergic response, which is associated with the migration of inflammatory cells into the airways, is in accord with the recent findings from several independent groups that endothelin receptor antagonists inhibit the antigeninduced influx of eosinophils into the airways and bronchoalveolar lavage fluid (12,15,31).In addition to its effects on eosinophil recruitment into the airways, ET-1 has many other purported actions within the airways that may promote inflammation and airflow obstruction. For example, ET-1 stimulates the release of a range of proinflammatory cytokines [such as interleukin (IL)-6, IL-1␤, and tumor necrosis factor-␣] and promotes microvascular leakage, mucous secretion, and collagen deposition within the airways (16).…”
supporting
confidence: 82%
“…The current demonstration of an important role for ET-1 in eosinophilic airway inflammation is underscored by the observation of a pronounced anti-inflammatory effect of treatment with an ET receptor antagonist in IT SDXinduced inflammation [1]. This effect has later been confirmed in another study [3] that demonstrated inhibition of the infiltration of inflammatory cells into the lungs after antigen challenge in ovalbumin-sensitized mice by blockage of ET receptors.…”
Section: Discussionmentioning
confidence: 86%
“…A study in 1999 by Mow et al indicated increased expression of endothelin receptors on thickened areas of valve leaflets in dogs with endocardiosis. 9 Endothelin has been implicated in inflammatory diseases of the pulmonary system, 28 and inflammation in end organ damage, because endothelin activates NF-kappa B, a transcription factor that enhances the production of inflammatory mediators. 29 Nitric oxide (NO) is an endogenous free radical produced by vascular endothelium, and is involved in the regulation of vascular tone.…”
Section: Discussionmentioning
confidence: 99%